Characterization of a lipid nanoparticle for mRNA delivery using molecular dynamics - Trollmann, Marius; Böckmann, Rainer (EUROPEAN BIOPHYSICS JOURNAL WITH BIOPHYSICS LETTERS, 2021)
CRIS-Team WoS Importer:2021-08-13

Characterization of domain formation in complex membranes - Trollmann, Marius; Böckmann, Rainer (Biophysical Approaches for the Study of Membrane Structure, 2024)
A widely known property of lipid membranes is their tendency to undergo a separation into disordered (Ld) and ordered (Lo) domains. This impacts the local structure of the membrane relevant for the physical (e.g., enhanced electroporation) and biological (e.g., protein sorting) significance of these regions. The increase in computing power, advancements in simulation software, and more detailed information about the composition of biological membranes shifts the study of these domains into the focus of classical molecular dynamics simulations. In this chapter, we present a versatile yet robust analysis pipeline that can be easily implemented and adapted for a wide range of lipid compositions. It employs Gaussian-based Hidden Markov Models to predict the hidden order states of individual lipids by describing their structure through the area per lipid and the average SCC order parameters per acyl chain. Regions of the membrane with a high correlation between ordered lipids are identified by employing the Getis-Ord local spatial autocorrelation statistic on a Voronoi tessellation of the lipids. As an example, the approach is applied to two distinct systems at a coarse-grained resolution, demonstrating either a strong tendency towards phase separation (1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC), 1,2-dilinoleoyl-sn-glycero-3-phosphocholine (DIPC), cholesterol) or a weak tendency toward phase separation (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC), 1-palmitoyl-2-docosahexaenoyl-sn-glycero-3-phosphocholine (PUPC), cholesterol). Explanations of the steps are complemented by coding examples written in Python, providing both a comprehensive understanding and practical guidance for a seamless integration of the workflow into individual projects.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Gaussian mixture model; Gaussian-based hidden Markov model; Getis-Ord statistic; Hidden Markov model; Liquid-ordered domain; Membrane domain

Generation of antimicrobial peptides Leg1 and Leg2 from chickpea storage protein, active against food spoilage bacteria and foodborne pathogens - Heymich, Marie-Louise; Friedlein, Ulrike; Trollmann, Marius; Schwaiger, Karin; Böckmann, Rainer; Pischetsrieder, Monika (Food Chemistry, 2021)
Contamination with bacteria leads to food waste and foodborne diseases with severe consequences for the environment and human health. Aiming to reduce food spoilage and infection, the present study developed novel highly active food-grade antimicrobial peptides affecting a wide range of bacteria. After extraction from chickpea, the storage protein legumin was hydrolyzed by the digestive protease chymotrypsin. Subsequent analysis by ultrahigh-performance micro-liquid chromatography–triple quadrupole time-of-flight tandem mass spectrometry determined the resulting peptide profiles. Virtual screening identified 21 potential antimicrobial peptides in the hydrolysates. Among those, the peptides Leg1 (RIKTVTSFDLPALRFLKL) and Leg2 (RIKTVTSFDLPALRWLKL) exhibited antimicrobial activity against 16 different bacteria, including pathogens, spoilage-causing bacteria and two antibiotic-resistant strains. Leg1/Leg2 showed minimum inhibitory concentrations (MIC) down to 15.6 µmol/L and were thus 10–1,000-fold more active compared to conventional food preservatives. Moreover, Leg1 and Leg2 showed bactericidal activity in contrast to the bacteriostatic activity of conventional preservatives.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Antimicrobial peptides; Chickpea proteins; Chymotryptic hydrolysis; Cicer arietinum L.; Preservative; Virtual screening

mRNA lipid nanoparticle phase transition - Trollmann, Marius; Böckmann, Rainer (Biophysical Journal, 2022)
Crucial for mRNA-based vaccines are the composition, structure, and properties of lipid nanoparticles (LNPs) as their delivery vehicle. Using all-atom molecular dynamics simulations as a computational microscope, we provide an atomistic view of the structure of the Comirnaty vaccine LNP, its molecular organization, physicochemical properties, and insight in its pH-driven phase transition enabling mRNA release at atomistic resolution. At physiological pH, our simulations suggest an oil-like LNP core that is composed of the aminolipid ALC-0315 and cholesterol (ratio 72:28). It is surrounded by a lipid monolayer formed by distearoylphosphatidylcholine, ALC-0315, PEGylated lipids, and cholesterol at a ratio of 22:9:6:63. Protonated aminolipids enveloping mRNA formed inverted micellar structures that provide a shielding and likely protection from environmental factors. In contrast, at low pH, the Comirnaty lipid composition instead spontaneously formed lipid bilayers that display a high degree of elasticity. These pH-dependent lipid phases suggest that a change in pH of the environment upon LNP transfer to the endosome likely acts as trigger for cargo release from the LNP core by turning aminolipids inside out, thereby destabilizing both the LNP shell and the endosomal membrane.
CRIS-Team Scopus Importer:2022-09-30

Nonuniversal impact of cholesterol on membranes mobility, curvature sensing and elasticity - Pöhnl, Matthias; Trollmann, Marius; Böckmann, Rainer (Nature Communications, 2023)
Biological membranes, composed mainly of phospholipids and cholesterol, play a vital role as cellular barriers. They undergo localized reshaping in response to environmental cues and protein interactions, with the energetics of deformations crucial for exerting biological functions. This study investigates the non-universal role of cholesterol on the structure and elasticity of saturated and unsaturated lipid membranes. Our study uncovers a highly cooperative relationship between thermal membrane bending and local cholesterol redistribution, with cholesterol showing a strong preference for the compressed membrane leaflet. Remarkably, in unsaturated membranes, increased cholesterol mobility enhances cooperativity, resulting in membrane softening despite membrane thickening and lipid compression caused by cholesterol. These findings elucidate the intricate interplay between thermodynamic forces and local molecular interactions that govern collective properties of membranes.
CRIS-Team Scopus Importer:2023-12-22

Revisiting lipid nanoparticle composition and structure: A critical take on simulation approaches - Trollmann, Marius; Rossetti, Paolo; Böckmann, Rainer (Proceedings of the National Academy of Sciences of the United States of America, 2025)
CRIS-Team Scopus Importer:2025-03-14

The antimicrobial fibupeptide lugdunin forms water-filled channel structures in lipid membranes - Ruppelt, Dominik; Trollmann, Marius; Dema, Taulant; Wirtz, Sebastian N.; Flegel, Hendrik; Mönnikes, Sophia; Grond, Stephanie; Böckmann, Rainer; Steinem, Claudia (Nature Communications, 2024)
Recently, a novel cyclo-heptapeptide composed of alternating d,l-amino acids and a unique thiazolidine heterocycle, called lugdunin, was discovered, which is produced by the nasal and skin commensal Staphylococcus lugdunensis. Lugdunin displays potent antimicrobial activity against a broad spectrum of Gram-positive bacteria, including challenging-to-treat methicillin-resistant Staphylococcus aureus (MRSA). Lugdunin specifically inhibits target bacteria by dissipating their membrane potential. However, the precise mode of action of this new class of fibupeptides remains largely elusive. Here, we disclose the mechanism by which lugdunin rapidly destabilizes the bacterial membrane potential using an in vitro approach. The peptide strongly partitions into lipid compositions resembling Gram-positive bacterial membranes but less in those harboring the eukaryotic membrane component cholesterol. Upon insertion, lugdunin forms hydrogen-bonded antiparallel β-sheets by the formation of peptide nanotubes, as demonstrated by ATR-FTIR spectroscopy and molecular dynamics simulations. These hydrophilic nanotubes filled with a water wire facilitate not only the translocation of protons but also of monovalent cations as demonstrated by voltage-clamp experiments on black lipid membranes. Collectively, our results provide evidence that the natural fibupeptide lugdunin acts as a peptidic channel that is spontaneously formed by an intricate stacking mechanism, leading to the dissipation of a bacterial cell’s membrane potential.
CRIS-Team Scopus Importer:2024-05-03